Hydrogen Production Via Carbon Dioxide Reforming - Jamal, Norhidayu (Universiti Teknologi PETRONAS, 2016)
In view of the escalating global warming phenomenon, utilization of CO2 has become an important event in recent decades. Syngas Hydrogen production via CO2 reforming is one of the most promising methods to produce COX-free hydrogen as a source of renewable and sustainable energy. Dry reforming of Methane (DRM) reaction is the process where the conversion of CO2 to synthesis gas (mixture of H2 and CO) takes place. Dry Reforming of Methane requires an active functioning catalyst and support to have a high hydrogen yield. The catalyst supports as well as its combination of the active component in order to have a high catalytic performance for the conversion of CO2 in hydrogen production is necessary. The catalytic behaviour of the bare and CaOpromoted 10%wt Ni/Al2O3 catalyst in CO2 reforming of CH4 is investigated.